A Critical Review of the Slaughter of Kendhit Goats to Reject Bala in the Perspective of Islamic Aqidah - Salma Rafa Perwita; Hamidah Hamidah; Kaneishia Farah Az-zahra; Muthi’ah Muthi’ah; Ferina Kansanaswa Devita; Febryan Hidayat (Demak Universal Journal of Islam and Sharia, 2024)
Indonesia has a variety of cultural diversity, one of the cultures in Indonesia that is known to be unique and even preserved by the community is the tradition to make peace with nature known as tolak bala. This tradition usually uses animals that are not arbitrary but there are special animal characteristics. One of them is the kendhit goats. People carry out this tradition to correct the bad things that are happening to them. This journal aims to find out the dark side of the tradition of slaughtering kendhit goats to reject reinforcements. This research uses qualitative methods, namely a descriptive analysis approach to data obtained from books and journals. In Islamic shari'a, this includes slaughtering animals other than Allah, so that the perpetrators in this act fall into grand shirk., this shirk can remove the perpetrator from Islam and Allah Subhaanahu wa Ta'ala will persecute him and will not forgive his sins unless the perpetrator repents with true repentance. In this tradition, there is also a selametan event, namely joint prayers, which was never taught by the Prophet Sallallahu alaihi wassalam, so it fell into the act of heresy. As we know the practice of worship that has no guidance, will be rejected from worship. Sometimes in selametan events, there is a meal together. Where the community enjoys the results of the sacrifice. The law of origin of the slaughtered meat should not be eaten because the meat is the result of sacrifice for other than Allah Subhaanahu wa Ta'ala.